Potential Antiosteoporotic Agents from Plants: A Comprehensive Review. (31st December 2012) - Jia, Min; Nie, Yan; Cao, Da-Peng; Xue, Yun-Yun; Wang, Jie-Si; Zhao, Lu; Rahman, Khalid; Zhang, Qiao-Yan; Qin, Lu-Ping
Abstract : Osteoporosis is a major health hazard and is a disease of old age; it is a silent epidemic affecting more than 200 million people worldwide in recent years. Based on a large number of chemical and pharmacological research many plants and their compounds have been shown to possess antiosteoporosis activity. This paper reviews the medicinal plants displaying antiosteoporosis properties including their origin, active constituents, and pharmacological data. The plants reported here are the ones which are commonly used in traditional medical systems and have demonstrated clinical effectiveness against osteoporosis. Although many plants have the potential to prevent and treat osteoporosis, so far, only a fraction of these plants have been thoroughly investigated for their physiological and pharmacological properties including their mechanism of action. An attempt should be made to highlight plant species with possible antiosteoporosis properties and they should be investigated further to help with future drug development for treating this disease.